Dengue fever and thrombocytopenia – A prospective Observational Study at Tertiary Care Centre - Tulara, Neeraj Kumar (Eastern Journal of Medical Sciences, 2019)
Background: Dengue fever is one of the commonest diseases in tropical countries and carries significant morbidity and mortality. Thrombocytopenia (low platelets) is one of the very common manifestations in case of dengue infection. Platelet transfusion in dengue always remains controversial. Objective: Present study was conducted to study precise criteria and transfusion trigger for platelet transfusion in our set-up. Materials and Methods: This study was conducted on 112 serologically antibody positive confirmed dengue patients admitted in a Hospital, Powai, Mumbai, between 1st of August to 30th October 2017. The age groups of the included patients were within 20-50 years and did not have any co morbidity and were diagnosed at OPD. Indication for hospitalization includes high grade fever (>101° F) and platelet counts less than 100,000 along with other viral prodromal symptoms. Clinical data, reports of laboratory investigations, platelets requirements and data obtained from daily follow-up and record sheets were analyzed. Results: In the serologically positive confirmed cases, the prevalence of thrombocytopenia (count <100,000/mm3) was 97% on admission and there was no bleeding recorded in any patient. Out of 112 serologically confirmed dengue cases, only 1 (<1%) patient of dengue received platelet transfusion whose platelet counts were <7000/mm3 and he had petechiae all over the body. Total 9 patients had platelet count <10000/mm3 (8.03%), 28 (25%) patients had platelet count <20,000/mm3, 52 (46%) had a platelet counts <40,000/mm3 while total 79 (70.53%) patients had platelet counts <50,000/mm3. In the study population, 28 (25%) patients had platelet count <20,000/mm3 and 9 (8.03%) patients had platelets count <10000/mm3, only 1 patient had petechiae; hence platelet transfusion was given. For all other patients who had platelet counts <20,000/mm3, their clinical parameters were monitored strictly and frequent manual platelet counts were done. These patients were not given any transfusion. Conclusion: This study suggests that bleeding due to thrombocytopenia in case of dengue fever is not a common occurrence especially, in otherwise healthy adult or middle aged patients. Those with no or minimum co morbidities and strict monitoring of symptoms are required to preserve the resources and to avoid unwanted platelet transfusions. Platelet count should not be a bench mark for someone to transfuse the platelet. Signs of bleeding, other co-morbid factors and clinical parameters should be taken in to consideration before starting platelet transfusions.